2020
DOI: 10.12669/pjms.36.3.1385
|View full text |Cite
|
Sign up to set email alerts
|

A hemispheric comparison of cognitive dysfunction and sleep quality impairment in Middle Cerebral Artery infarction

Abstract: Objectives: To investigate the severity of cognitive dysfunction and sleep quality impairment in patients with middle cerebral artery (MCA) strokes across the left and right hemisphere. Moreover, it also study gender differences with respect to MCA strokes. Methods: The study was conducted from February 2019 - May 2019 at COMSATS University, Islamabad. A total sample size of N=55 middle cerebral artery ischemic infarct patients was selected with N=29 left middle cerebral artery ischemic infarct patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
3
1
Order By: Relevance
“…This study showed that the highest risk factor found between both groups was hypertension (>80% Study conducted based in Pakistan showed a higher rate of left hemisphere ischemic stroke patients than right. 16 Different from our study, most of the patients had strokes on their right hemispheres (47.2%). In a former study, it was found that left middle cerebral artery stroke patients may be more prone to greater degree of cognitive impairment than right MCA.…”
Section: Sample Descriptioncontrasting
confidence: 79%
“…This study showed that the highest risk factor found between both groups was hypertension (>80% Study conducted based in Pakistan showed a higher rate of left hemisphere ischemic stroke patients than right. 16 Different from our study, most of the patients had strokes on their right hemispheres (47.2%). In a former study, it was found that left middle cerebral artery stroke patients may be more prone to greater degree of cognitive impairment than right MCA.…”
Section: Sample Descriptioncontrasting
confidence: 79%
“…Depending on the occlusion time, varying levels of lesion severity can be obtained in this model, however, 1 h occlusion in the MCAO model produces reproducible infarction in the MCA territories, including the frontoparietal cortex and lateral caudoputamen, and mimics human stroke symptoms [ 44 , 45 ]. We specifically targeted the right MCA in this study since sleep disturbances are commonly observed in patients with right hemispheric infarcts [ 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that patients with left hemisphere cerebral infarction have a worse prognosis [ 29 31 ]. In a cognitive study involving nine sub-tests [ 32 ], cognitive impairment and sleep quality impairment caused by middle cerebral artery stroke were observed in the left and right hemispheres, regardless of gender. In another previous study investigating motor observation and imagination ability of hemispheric stroke patients [ 33 ], patients with left subcortical lesions recruited more cortical regions when processing motor images and videos, suggesting that lesions in the dominant hemisphere had a greater impact on the motor system.…”
Section: Discussionmentioning
confidence: 99%